PM 542: Social Network Analysis - Valente, Thomas (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is an introduction to the theory, methods and procedures of network analysis with emphasis on applications to public health programs. The goal of the course is to provide a working knowledge of the concepts and methods used to describe and analyze networks so that professionals and researchers can understand the results and implications of this body of research. The course also provides the training necessary for scholars to conduct network analysis in their own research careers. The course consists of readings, class discussions, computer and data analysis assignments, and a final paper. The data analysis assignments will be conducted using the UCINET V network analysis software available to students in the class. Individual student papers will use data that the student collects him/herself. The data collection and entry process will be quite simple and consist of identifying a group (a class, club, organization, etc.) that students can meet and then ask to complete a simple one page questionnaire.